A Systematic Review And Meta-Analysis Of Carbapenem-Resistant Enterobacteriaceae In West Africa. - Donkor, E.S. (BMC Medical Genomics, 2024)
Background: In Africa, the problem of carbapenem-resistant Enterobacteriaceae (CRE) is aggravated by many factors. This systematic review attempted to describe the current status of the molecular epidemiology of carbapenem resistance in West Africa (WA). Methods: Articles published from 16 West African countries on the molecular epidemiology of carbapenem resistance were reviewed. An extensive literature search was carried out in PubMed, Scopus, Web of Science, and African Journals Online (AJOL) using specific keywords. The meta-analysis and forest plots of major pathogens and carbapenem resistance genes were done using the Open Meta-Analyst, Task Order # 2 software. The data were analysed in binary random model effects by the DerSimonian-Laird method at a 95% confidence interval. Results: Of the 431 articles found in our initial search, 60 (13.92%) were considered suitable for inclusion. Only seven of the 16 West African countries formed part of the analysis, Nigeria (23/60), Ghana (19/60), Burkina Faso (7/60), Senegal (6/60), Benin (2/60), Mali (2/60), and Togo (1/60). Also, 80% (48/60) of the studies used clinical samples, 16.67% (10/60) used environmental samples, and 3.33% (2/60) used animal samples. The average prevalence was highest in Acinetobacter baumannii (18.6%; 95% CI=14.0-24.6, I2=97.9%, p<0.001), followed by Pseudomonas aeruginosa (6.5%; 95% CI=3.1–13.4, I2=96.52%, p<0.001), Klebsiella pneumoniae (5.8%; 95% CI=4.2–7.9, I2=98.06%, p<0.001) and Escherichia coli (4.1%; 95% CI=2.2–7.7, I2=96.68%, p<0.001). The average prevalence of the blaNDM gene was 10.6% (95% CI=7.9–14.3, I2=98.2%, p<0.001), followed by 3.9% (95% CI: 1.8–8.3, I2=96.73%, p<0.001) for blaVIM and 3.1% (95% CI: 1.7–5.8, I2=91.69%, p<0.001) for blaOXA-48. Conclusion: In West Africa, K. pneumoniae, E. coli, A. baumannii, and P. aeruginosa are the main CRE with blaNDM, blaVIM, and blaOXA-48 being the predominant carbapenem resistance genes. In view of these results, ongoing CRE surveillance combined with antimicrobial stewardship improved, laboratory detection methods, and adherence to infection control practices will be needed to control the spread of CRE.
Research Article
Keywords: West Africa; Molecular epidemiology; Carbapenem-resistance; Meta-analysis